2016
DOI: 10.1080/10255842.2016.1154547
|View full text |Cite
|
Sign up to set email alerts
|

Subject-specific geometrical detail rather than cost function formulation affects hip loading calculation

Abstract: This study assessed the relative importance of introducing an increasing level of medical image-based subject-specific detail in bone and muscle geometry in the musculoskeletal model, on calculated hip contact forces during gait. These forces were compared to introducing minimization of hip contact forces in the optimization criterion. With an increasing level of subject-specific detail, specifically MRI-based geometry and wrapping surfaces representing the hip capsule, hip contact forces decreased and were mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 52 publications
3
38
0
Order By: Relevance
“…This may have important implications for people with hip OA, who often exhibit hip muscle weakness (Loureiro et al, 2013) and altered hip muscle activation patterns (Rutherford et al, 2015;Sims et al, 2002). Wesseling et al (2016) demonstrated that HJCF minimisation had no effect on overall prediction of HJCF. However, their HJCF minimisation was performed within the static optimisation criteria, thus influencing the estimation of muscle activation rather than neuromuscular parameters of the NMS model.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This may have important implications for people with hip OA, who often exhibit hip muscle weakness (Loureiro et al, 2013) and altered hip muscle activation patterns (Rutherford et al, 2015;Sims et al, 2002). Wesseling et al (2016) demonstrated that HJCF minimisation had no effect on overall prediction of HJCF. However, their HJCF minimisation was performed within the static optimisation criteria, thus influencing the estimation of muscle activation rather than neuromuscular parameters of the NMS model.…”
Section: Discussionmentioning
confidence: 97%
“…This could introduce errors in the muscle lines of action and moment arms, which in turn affect the resulting HJCF. Though this is commonly done in NMS modelling (Graham et al, 2016;Kainz et al, 2016;Steele et al, 2012), future investigation should include imaging data to create models with subjectspecific geometries (Gerus et al, 2013;Wesseling et al, 2016) and joint kinematics (Brito da Luz et al, 2017). Subject-specific imaging data will also improve hip joint centre location calculations, an important parameter in estimating HJCF (Lenaerts et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Some limitations of this study should be considered. Analyses were performed using a linearly-scaled generic musculoskeletal model, which does not account for subject-specific muscle pathways and moment arms, influential factors in estimating JCF's (Lenaerts et al, 2008;Wesseling et al, 2016a). Variation in calculated hip joint centre locations can influence HJCF estimations (Lenaerts et al, 2008;Stagni et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, generic musculoskeletal models remain widely used due to their simplicity and availability (Graham et al, 2016;Kainz et al, 2016;Steele et al, 2012). Future investigation should consider creating musculoskeletal models with subject-specific geometries (Gerus et al, 2013;Wesseling et al, 2016a) and joint kinematics (Brito da Luz et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…One of the major factors that could affect the prediction of joint and muscle forces is the accuracy of the geometrical representation of the lower-limb muscles [ 22 26 ]. In particular, musculoskeletal models were previously reported to be sensitive to errors in the insertion, intermediate, and origin points of the muscles [ 24 , 25 ], with the muscles spanning the hip joint causing the highest uncertainty in the prediction of muscle [ 25 ] and contact forces [ 26 ]. A recent cadaveric dataset based on medical imaging data, TLEM 2.0 [ 27 ], provides muscular geometrical information with the highest level of detail currently available; however, this data has not yet been adopted for musculoskeletal applications focusing on the hip joint.…”
Section: Introductionmentioning
confidence: 99%